NEW NORMAL UMKM: DESAIN SISTEM REKRUTMEN KARYAWAN BERBASIS DIGITAL - Surya Astitiani, Ni Luh Putu; Richadinata, Kadek Riyan Putra; Rettobjaan, Vitalia Fina Carla (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022, 2022)
The approach used in this study is a qualitative approach, namely an approach in the form of collecting data, processing, and analyzing and interpreting it qualitatively. The research location is in several MSMEs spread across the city of Denpasar. The research data collection was carried out for 2 months, from January to February 2021. The scope of this research was to design a digital-based employee recruitment system for MSMEs, then evaluate the results of the design. The data analysis technique used in this research is adjusting to the data collection methods used, namely literature study, observation, and questionnaires. From the three data collection models, data analysis was carried out using the following models: Data Reduction, Data Display and Conclusion Drawing/Verification. Research on the design of a digital-based employee recruitment system for MSMEs as a solution to adapting new habits (new normal) results in a business process design using Data Flow Diagrams (DFD) and designing the system interface. While the results of the evaluation in the form of a questionnaire to users who will use this system indicate that the overall information system is very good, as many as 36 people answered with a very good response.